Effects of an 8-week Mindfulness–Acceptance–Commitment intervention on competitive anxiety, mindfulness, and 200-m sprint performance in junior female sprinters: a quasi-experimental study - Chiraz Goumni; Amayra Tannoubi; Aymen Hawani; Riadh Khalifa; Medina Srem-Sai; John Elvis Hagan; Vlad Adrian Geantă (Sport Sciences for Health, 2026)
Abstract Background Competitive anxiety is a critical factor influencing performance in explosive, self-paced sports such as sprinting. Although mindfulness and acceptance-based approaches are increasingly used in sport psychology, evidence for their effects in young female track athletes remains limited. Purpose This quasi-experimental study examined the effects of an 8 week Mindfulness–Acceptance–Commitment (MAC) program on pre-competitive anxiety, mindfulness skills, and 200 m sprint performance in junior female sprinters. Methods Thirty national-level junior female sprinters aged 17–18 years participated in the study. Fifteen athletes recruited from two regional clubs participated in the MAC intervention, whereas fifteen athletes recruited from a third club continued their usual training. Because intervention condition was completely confounded with club membership, differences in coaching practices, training environment, team culture, and expectancy may have contributed to between-group differences. Pre- and post-intervention assessments included the Competitive State Anxiety Inventory-2 Revised (CSAI-2R), the Five Facet Mindfulness Questionnaire (FFMQ), and an electronically timed 200-m sprint test. The intervention consisted of one 60-min group session per week for 8 consecutive weeks. Results Significant Group × Time interactions were observed for cognitive anxiety, somatic anxiety, and self-confidence (all p < .001). In the MAC group, cognitive anxiety decreased from 15.47 ± 1.41 to 10.07 ± 1.33, somatic anxiety decreased from 17.20 ± 2.11 to 13.80 ± 1.57, and self-confidence increased from 10.47 ± 1.68 to 16.67 ± 1.45. Significant Group × Time interactions were also observed across all five FFMQ facets, including Describing, Acting with Awareness, Non-judging of Inner Experience, Non-reactivity to Inner Experience, and Observing, with greater pre–post improvements in the MAC group than in the control group. For example, Nonjudging of Inner Experience increased in the MAC group from 19.80 ± 2.18 to 21.20 ± 2.04, whereas the control group remained unchanged (20.60 ± 1.64 to 20.60 ± 1.64). Mean 200-m sprint time decreased from 26.63 ± 0.60 s to 26.20 ± 0.54 s in the MAC group, representing a 0.43-s reduction (1.61%), whereas the control group changed from 26.68 ± 0.78 s to 26.72 ± 0.75 s (0.04 s increase). Conclusion Participation in the 8-week MAC intervention was associated with more favorable pre-competitive psychological outcomes, changes in mindfulness facets, and faster objectively measured 200 m sprint performance in this sample of junior female sprinters. Given the quasi-experimental, club-based allocation, these findings should be interpreted as preliminary associations rather than definitive evidence of a causal effect of MAC. Randomized, adequately powered multicenter studies with active control conditions are needed to determine the specificity, durability, and mechanisms of these potential benefits.